A 3D printed graphene electrode device for enhanced and scalable stem cell culture, osteoinduction and tissue building. (March 2021) - Li, Jianfeng; Liu, Xiao; Crook, Jeremy M.; Wallace, Gordon G.
Abstract: Bone related diseases and disorders increasingly impact human health. Electrical stimulation (ES) has been shown to promote osteogenesis and healing of bone defects. Graphene, is an electrically conductive and biocompatible material with good mechanical properties (strength with flexibility), and therefore shows significant promise as a cell-compatible electrode for ES. Graphene-based scaffolds may therefore be used for 3D cell and tissue support, including 3D osteoinduction. We have fabricated 3D graphene electrode structures to provide ES to human adipose stem cells (ADSCs). The assemblies support ADSC growth and differentiation, with ES augmenting proliferation and osteogenesis. Our findings expand our previous work on developing graphene-based cell culture platforms for bone engineering, demonstrating their adaptability and amalgamation for more scalable and high throughput stem cell maintenance, osteoinduction and tissue building. Furthermore, the devices have the potential to be employed for a variety of other cells and tissues for research and therapeutics, including regenerative medicine. Graphical abstract: Unlabelled Image Highlights: An easy to fabricate platform for scaleable and high-throughput 3D cell culture and electrical stimulation for tissue building. Includes multiple 3D printed graphene-coated alginate scaffolds that are sequentially connected using graphene-coated cellulose strips and graphene "glue". The assembled device is mechanically robust, electroconductive and biocompatible. Confirmed long-term human adipose stem cell proliferation and osteogenic differentiation that is enhanced with 3D electrical stimulation.